Hydromethanolic Root Extract of Gnidia Kraussiana Demonstrates Anti-Inflammatory Effect Through Anti-Oxidant Activity Enhancement in a Rodent Model of Gout - Elizé Dadaya; Benoit Koubala; Dieudonné Ndjonka; Stéphane Zingué; Alphonse Laya; Gisèle Atsang (SAGE Publishing, 2023)
Gout is a metabolic arthritis that originates from increased accumulation of monosodium urate (MSU) crystals in joints. This work aimed to evaluate the antioxidant and anti-inflammatory activities of the hydromethanolic extract of Gnidia kraussiana (HEGK) using model of Gouty arthritis on mice. The total polyphenol, flavonoid, tannin content and the antioxidant activity of HEGK were also evaluated. MSU-injected mice were treated daily for 3 days with HEGK (25, 50 and 100 mg/kg). Indomethacin and colchicin were used as reference drugs. Paw oedema and body temperature were measured at different time intervals post-injection. Malondialdehyde, acid phosphatase, β-Galactosidase, catalase, superoxide dismutase and glutathione levels were evaluated. HEGK is rich in polyphenol (129.93 mg/100 g), flavonoid (67.78 mg/100 g) and tannin conferring it a high antioxidant activity. Acute oral toxicity of HEGK resulted in LD50 greater than 2000 mg/kg. Oral administration of HEGK induced a significant decrease in the oedema of legs injected with urate crystals and reduced the release of acid phosphatase and β-Galactosidase. A model of oxidative damage was successfully established, revealing a significant increase in malondialdehyde and inhibition of antioxidants, including superoxide dismutase, catalase and glutathione activity. Thus, HEGK can actively inhibit the effect of inflammatory mediators in gouty arthritis.